IDENTIFICATION OF COSMOSIIN AS A BIOACTIVE FLAVONOID IN Memecylon randerianum S.M. Almeida & M.R. Almeida: INSIGHTS INTO ITS ANTICANCER POTENTIAL (Applied Biological Research, 2026)
The phytopharmaceutical industry increasingly employs advanced medicinal chemistry tools, including molecular docking, to facilitate the rational design and development of effective therapeutics against complex diseases such as cancer. In the present study, the anticancer potential of phytoconstituents from Memecylon randerianum was evaluated against Dalton’s lymphoma ascites (DLA) and Ehrlich ascites carcinoma (EAC) tumour cell lines. The cytotoxic activity of the plant extract was further assessed using HeLa cervical cancer cells, MCF-7 breast cancer cells, and L929 fibroblast cell lines through the MTT assay. High-resolution liquid chromatography–mass spectrometry (HR LCMS) analysis was performed to identify the chemical constituents present in the leaf extract. An in silico approach was subsequently employed to validate the pharmacological relevance and bioactivity of the identified compounds. Cosmosiin emerged as the predominant phytoconstituent in M. randerianum leaves. The ADMET characteristics of cosmosiin were predicted and analysed using the pkCSM and SwissADME tools. Protein-ligand interactions were visualised through two-dimensional diagrams generated using LigPlot+. The findings suggest that the cytotoxic effects exhibited by M. randerianum against cancer cell lines may be attributed to the presence of bioactive flavonoid, cosmosiin, highlighting its potential as a promising source for the development of novel anticancer drug leads.
Keywords: Bioactive compound; cosmosiin; drug lead, flavonoid, in silico, phytoconstituents